Agile processes in software engineering and extreme programming : 17th International Conference, XP 2016, Edinburgh, Scotland, May 24-27, 2016. Proceedings /: 17th International Conference, XP 2016, Edinburgh, Scotland, May 24-27, 2016. Proceedings. (2016) - Unknown
No abstract available